Basal Cell Carcinoma at the Tip of the Nose – A Case Report (Community Based Medical Journal, 2022)
Skin cancers contribute very less to the total number of carcinomas. Particularly when on the face or exposed parts affect cosmetically more than functionally. Basal Cell Carcinoma over face is a locally destructive malignancy of the skin which rarely metastasizes. Basal cell carcinomas are the most common type of cancer in Europe, Australia, and the USA. A case of basal cell carcinoma is reported here in an adult female living in a rural area, who came for cosmetic purpose in the Department of Dermatology & Venereology, Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh and was transferred to the Department of Otolaryngology & Neck-Head Surgery of the same institution for better management. She was treated with best of the modalities available, i.e., wide local excision with local Nasolabial flap reconstruction with follow up.CBMJ 2021 January: vol. 10 no. 02 P: 115-117